Pengelolaan Layanan Bimbingan Konseling Di Smpn 1Pulokulon Kabupaten Grobogan - Mariawati, Sri; , Prof. Dr. Bambang Sumardjoko; , Dr. Sumardi.M.Si (2017)
This study aims to identify and describe the management strategy of guidance and counseling services in Junior High School 1 Pulokulon regency Grobogan, which includes Planning, Implementation and Evaluation Service. The research method used is qualitative method with the participatory approach and analysis of data from various sources which include the principal, vice principal, teacher guidance and counseling. . The results showed that levels of program activities counseling services in Junior High School 1 Pulokulon regency Grobogan are: 1) the planning stage 2) the implementation of the program 3) the evaluation 4) the results of the analysis 5) the level of follow-up. The service type is a service orientation, information services, placement services and distribution, service learning, counseling, group counseling services and case conferences. In providing guidance measures implementation guidance and counseling services are 1) the analysis of the problem, 2) synthesis, 3) diagnosis, 4) prognosi, 5) ounseling or treatment, 6) Follow-up. Evaluation of guidance and counseling services in Junior High School 1 Pulokulon regency Grobogan responsibility of heads of schools assisted by the supervisor of special and school personnel other, management guidance and counseling services in SMPN 1 Pulokulon Grobogan been done properly starting from the planning, implementation, and evaluation at each end of the school year is a measure of the success of the service.